Peningkatan Kualitas Pendidikan Melalui Program Bimbingan Belajar Bagi Siswa SD Negeri 173144 Silangkitang Desa Sipahutar - Hotmarito Romauli Hutabarat; Tia Murni Tampubolon; Rapita Banjarnahor; Rico M Sihotang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Community Service (PKM) is a form of implementation of the tridharma of higher education carried out by lecturers in the community. For students, this is one of the mandatory courses that must be taken to train them to apply the knowledge and skills they already have in the learning process according to their respective fields of study. This PKM activity aims to improve the quality of education for students at SD Negeri 173144 Silangkitang, Sipahutar Village through more useful activities, such as tutoring and games that can increase knowledge and cooperation between children in the school environment. The method used in collecting data is as follows: conducting a survey to find out the number of students in the school then recruiting tutoring participants, then tutoring activities are carried out once a week, namely on Fridays, starting at 14.00-16.00 WIB. The PKM implemented at SD Negeri 173144 Silangkitang aims to improve student academic achievement through the provision of study guidance. Apart from that, this program also aims to foster students' interest in learning by using interesting and interactive learning methods. Although a new activity, tutoring is not unfamiliar to this environment, demonstrating awareness of the importance of education to improve the quality of learning. Throughout the implementation, participants not only demonstrated extraordinary enthusiasm but also consistency with punctual attendance, reflecting their dedication to the learning process.